Killing Reagan [compact disc, unabridged] : the violent assault that changed a presidency - O'Reilly, Bill (Macmillan Audio, 2015)
Just two months into his presidency, Ronald Reagan lay near death after a gunman's bullet came within inches of his heart. His recovery was nothing short of remarkable -- or so it seemed. But Reagan was grievously injured, forcing him to encounter a challenge that few men ever face. Could he silently overcome his traumatic experience while at the same time carrying out the duties of the most powerful man in the world?